Laryngeal manual therapy palpatory evaluation scale: A preliminary study to examine its usefulness in diagnosis of occupational dysphonia - Ewelina Woźnicka; Ewa Niebudek-Bogusz; Joanna Morawska; Justyna Wiktorowicz; Mariola Śliwińska-Kowalska (Nofer Institute of Occupational Medicine, 2017)
Background: The aim of this study has been to assess the larynx and soft tissue around the vocal tract in a group of people with healthy voice, and in a group of patients with occupational dysphonia using the new laryngeal manual therapy palpatory evaluation scale (LMTPE). Material and Methods: The examinations were performed in a study (dysphonic) group of professional voice users who had developed voice disorders (N = 51) and in the control group of normophonic subjects (N = 50). All the participants underwent perceptual voice assessment and examination by means of the LMTPE scale. Additionally, phoniatric examination including VHI (Voice Handicap Index) questionnaire, GRBAS (the Grade of hoarseness, Roughness, Breathiness, Asthenic, Strained) perceptual evaluation, maximum phonation time (MPT) measurement and videostroboscopy was performed in the study group. Results: The comparison of the LMTPE total score showed that the results of the study group were significantly poorer than those of controls (p < 0.001). In the study group, correlations were found between the LMTPE results and the VHI scores (p < 0.05), perceptual evaluation by the GRBAS (p < 0.05) and the objective parameter MPT (p < 0.05). Conclusions: The study has proven that the LMTPE scale is characterized by the high score of Cronbach's α ratio estimating the reliability of the test. The results have confirmed that the LMTPE scale seems to be a valuable tool, useful in diagnostics of occupational dysphonia, particularly of hyperfunction origin. Med Pr 2017;68(2):179-188